Vertebral Compression Fractures as a Presenting Feature of AcuteLymphoblastic Leukemia (Journal of Medicine, 2016)
Acute lymphoblastic leukemia is one of the most common malignancies in children and adolescent accounting for 30% of all the cancers. We report an interesting case of Acute lymphoblastic leukaemia(ALL) with an unusual presentation.This 15year- old girl came with a progressive low back pain for three months following a history of fall for 5 month ago with intact consciousness. The physical examination showed gibbus over lumbar spine with tenderness. Images showed generalized osteopenia with multiple vertebral body collapse.Complete blood count revealed pancytopenia with raised ESRwithout any blast cell. Bone marrow aspirate was suggestive of ALL.Young ALL patients usually present with symptoms due to cytopenias, fever and bone pains. Although asymptomatic skeletal involvement may be present in patients with ALL, rarely patients present with pathological fractures. Therefore a high index of suspicion is needed to diagnose such case.J MEDICINE July 2016; 17 (2) : 120-121